(untitled) (Journal of Parents and Teachers, 2014)
This article presents the growing success of the TV series about very different kind of families: rich, poor, sophisticated, ordinary, traveling, conflictive or funny families. Family life is complex, surprising, and it is full of adventures. This explains the triumph of this type of TV series.